2011
DOI: 10.1159/000332974
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Analysis of Specific Nail Psoriasis Features and Their Correlations with Clinical Parameters: A Cross-Sectional Study

Abstract: Background:Occurrence rates of specific features of psoriatic nails, as well as the influence of variable clinical parameters on nail involvement in psoriasis, are not determined. Objective:To evaluate the frequency and characteristics of nail involvement in patients with psoriasis and determine the relationship between nail psoriasis and clinical parameters (age, gender, family history, clinical type, age of onset, duration, joint involvement). Methods: 228 psoriatic patients, who had not received any systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 39 publications
6
32
0
3
Order By: Relevance
“…25, 8183 Nail psoriasis can be quite painful and result in decreased functional ability and quality of life. 84 The prevalence of nail disease among patients with PsA ranges from 41–93%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25, 8183 Nail psoriasis can be quite painful and result in decreased functional ability and quality of life. 84 The prevalence of nail disease among patients with PsA ranges from 41–93%.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of nail disease in PsO is around 15–50%. 23, 81, 83, 8588 Nail disease (pitting and onycholysis in particular) have been associated with inflammation at the enthesis where the extensor tendon connects to the nail unit 89 and is often correlated with DIP joint involvement. 90, 91 Furthermore, thickening of the entheses of the extensor tendon on ultrasound was more common in patients with clinical nail changes.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the normal nail is anchored to the skeleton via a network of entheses [11]. Patients with nail disease also have more subclinical enthesitis both at the distal interphalangeal joint level as well as at remote sites [12,13], although the link between the different patterns of nail disease and subclinical enthesitis remains enigmatic [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Bu oran literatür ile uyumluydu (1,2,14). En sık görülen tırnak tutulumu pitting, en az görülen ise splinter hemoraji olarak saptandı.…”
Section: Gereç Ve Yöntemunclassified